Latest Ordovician–early Silurian palaeoenvironmental changes and palaeotemperature trends indicated by stable carbon and oxygen isotopes from northern Estonia - Bilal Gul; Leho Ainsaar; Tõnu Meidla (Estonian Journal of Earth Sciences, 2021)
Brachiopods are the biological constituents most often used for the delineation of stable C and O isotopic compositions in Palaeozoic sediments. We present C and O isotope data for the Late Ordovician and early Silurian to evaluate the palaeotemperatures and palaeoenvironmental variability in Baltica from bulk rock and brachiopod shells. The studied carbonate rocks and fossils are well preserved in most of the localities as the area has not been affected by substantial tectonic activities or deep burial diagenesis. The Î´13C and Î´18O values for the samples range from â1.5â° to 5â° and from â7â° to â2â°, respectively. If the isotope signal reflects the original oxygen composition in sea water, the high Î´13C and Î´18O values could correspond to the colder episodes and vice versa. The Late Ordovician Hirnantian stable carbon isotopic excursion (HICE) is well recognized globally as an eminent glacial isotopic event and has been reported in several sections in the Baltic region. The HICE is observable in the bulk rock carbon stable isotope curves as a very clear gradual rise and a maximum confined to the upper part of the Ãrina Formation (Porkuni Regional Stage) in northern Estonia. The rising interval of Î´13C in the Ãrina Formation may correspond to the early Hirnantian time interval. The peak HICE is followed by a gradual decline in the Î´13C values in the basal beds of the Varbola Formation (Juuru Regional Stage). The bulk carbonate Î´18O values show a prominent positive excursion in the Hirnantian interval possibly reflecting the global cooling event. The post-glacial latest Ordovician to early Silurian global warming might be responsible for the clear decreasing trend of both the Î´18Obulk and Î´18Obrach values in the interval of the Juuru Regional Stage in the studied sections. Our study shows that Î´18O values revealed from both the brachiopod and bulk rock material of marine Upper Ordovicianâlower Silurian carbonates could tentatively be interpreted as reflecting the major temperature trends.